RANCANG BANGUN DIGITAL BANDPASS FILTER SEBAGAI APLIKASI SOUND ACTIVATION (Fakultas Teknik Universitas Wisnuwardhana, 2022)
The Robot system Of Fire is an intelligent robot, where robot is given artificial intelligence to carry out its tasks, namely robot has to find a fire in a mysterious labyrinth, then perceives it. Sound signal that has 3,8 kHz frequency is needed to enable robot. Sound activation in robot has function to recognize the 3,8 kHz sound signal. Digital bandpass filter is one of digital filter which has function to pass signal that has frequency between lower cutoff frequency and upper cutoff frequency. Analog to digital converter process is used to convert analog signal to digital signal. This process consists of sampling, quantization, and coding. The purpose of this research is applicating digital bandpass filter on sound activation system in order to detect audio source which is 3,8 kHz sound signal.